2005
DOI: 10.1001/jama.294.22.2879
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Status in Health Research

Abstract: Problems with measuring socioeconomic status (SES)-frequently included in clinical and public health studies as a control variable and less frequently as the variable(s) of main interest-could affect research findings and conclusions, with implications for practice and policy. We critically examine standard SES measurement approaches, illustrating problems with examples from new analyses and the literature. For example, marked racial/ethnic differences in income at a given educational level and in wealth at a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

44
1,732
4
31

Year Published

2006
2006
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,813 publications
(1,877 citation statements)
references
References 122 publications
44
1,732
4
31
Order By: Relevance
“…Multicollinearity for socio-economic circumstances has been tested previously, but it was not found (Laaksonen et al, 2005b). Also other previous studies suggest that correlations between different socio-economic circumstances such as education and income are not strong enough to justify using one indicator as a proxy for another (Braveman et al, 2005). Thus, these indicators are not to be considered interchangeable.…”
Section: Socio-economic Circumstancesmentioning
confidence: 91%
See 2 more Smart Citations
“…Multicollinearity for socio-economic circumstances has been tested previously, but it was not found (Laaksonen et al, 2005b). Also other previous studies suggest that correlations between different socio-economic circumstances such as education and income are not strong enough to justify using one indicator as a proxy for another (Braveman et al, 2005). Thus, these indicators are not to be considered interchangeable.…”
Section: Socio-economic Circumstancesmentioning
confidence: 91%
“…Furthermore, at least partially divergent etiological processes may lie behind the association of each socio-economic indicator and food behaviour (Macintyre, 1997). As socio-economic position is a multidimensional umbrella concept, it has been suggested that studies should include several socio-economic measures and consider their nature, stage over the life course and interrelationships, as well as explanatory pathways through which they may influence health-related outcomes, including food behaviour (Braveman et al, 2005;Galobardes et al, 2006a, b). Examining simultaneously multiple dimensions of socio-economic circumstances helps elucidate our understanding of the observed inequalities and identify potential risk groups for health promotion programmes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large corpus of research shows that low SES is strongly related to morbidity, mortality and biological risk factors (Backlund, Sorlie & Johnson, 1999;Banks, Marmot, Oldfield & Smith, 2006;Braveman, Cubbin, Egerter, Chideya, Marchi, Metzler, 2005;Fritzell & Lundberg, 2007;Seeman, Merkin, Crimmins, Koretz, Charette & Karlamangla, 2008;Shishehbor, Litaker, Pothier & Lauer, 2006).…”
Section: Ses Sleep Problems and Healthmentioning
confidence: 99%
“…At the same time, they accumulate high amount of driving while drowsy (McCartt et al 1996). ERR is often invoked but not quantified to explain the social disparities in road safety, especially among children (Braveman et al 2005;Soori and Bhopal 2002;White et al 2000).…”
Section: Contextmentioning
confidence: 99%